Pengembangan Pantai Dreamland Sebagai Daerah Tujuan Wisata - Elya Kennis Rozana; I Nyoman Sunarta (JURNAL DESTINASI PARIWISATA, 2018)
In a development of tourist destination area has several stages that can show the position and situation of development in that tourist destination area. Dreamland Beach is located in the south of Bali precisely in the Pecatu area. This research aims to provide an overview of the existing conditions of Dreamland Beach in terms of tourism product components and the development of Dremland Beach, also explore suitable strategies for Dreamland Beach development. This research used qualitative descriptive data analysis and analysis using SWOT. Theories and concepts that used are the concept of beach, touris destination area, development and theory of Butler or tourism area life cycle. The result of this study is indicate the existing condition of Dreamland Beach that viewed from the components of tourist attraction products. The Facilities and infrastructure is support but still lacking. The acces road to Dreamland Beach is nice and easy to reach and additional service are still overlapping and not yet comprehensive. The development of Dreamland Beach is still in the stage involvement. As well as a suitable develompmet of Dreamland Beach is to maintain the cleanliness of the beach and open new access to attract tourists, providing easy access to the location of Dreamland Beach to overcome the competition with other tourist destination, open new access and do promotion more vigorously to attract more tourists to visit Dreamland Beach. Keywords : existing conditions, components of tourism products, the development of tourist destination areas, the development of tourist destinations